Examination of the level of state-trial anxiety of elite level archers from several variables - Saçakli, H. (Journal of Education and Training Studies, 2019)
The purpose of this study is to examine the state and trait anxiety levels of the individuals who perform archery sports at the elite level according to different variables. The population of the study was held from constitute archers who participated in the archery tournament "Turkey Cup" in 2018 (N=421). Also, the sample of the research was the volunteer athletes determined by the simple random sampling method (n = 156). The study was conducted by applying the causal comparison method in the screening model. The data collected by the survey technique. Participants were provided with a personal information form and Trait and State Anxiety Inventory. The obtained data transferred to SPSS 22 packet program and one-way ANOVA and Independent Sample T-test statistic applied as the statistical process for study purpose. This study demonstrates that there was a significant difference between the participants' level of trait anxiety according to gender variable and state anxiety levels according to the bow categories they used. Also the study demonstrates that there was a significant difference between the participants' level of trait anxiety according to gender variable and state anxiety levels according to the bow categories they used.